Efficient and Rapid Microfluidics Production of Bio-Inspired Nanoparticles Derived from Bombyx mori Silkworm for Enhanced Breast Cancer Treatment - Muhamad Hawari Mansor; Zijian Gao; Faith Howard; Jordan MacInnes; Xiubo Zhao; Munitta Muthana (Pharmaceutics)
Background/Objectives: In the quest for sustainable and biocompatible materials, silk fibroin (SF), derived from natural silk, has emerged as a promising candidate for nanoparticle production. This study aimed to fabricate silk fibroin particles (SFPs) using a novel swirl mixer previously presented by our group, evaluating their characteristics and suitability for drug delivery applications, including magnetic nanoparticles and dual-drug encapsulation with curcumin (CUR) and 5-fluorouracil (5-FU). Methods: SFPs were fabricated via microfluidics-assisted desolvation using a swirl mixer, ensuring precise mixing kinetics. Comprehensive physicochemical characterisation, including size, polydispersity index (PDI), zeta potential, and secondary structure analysis, was conducted. Further, CUR/5-FU-loaded magnetic core SFPs were assessed for cytotoxicity in vitro using breast cancer cell lines and for biodistribution and targeting efficiency in a murine breast cancer model. Results: The swirl mixer produced SFPs with sizes below 200 nm and uniform distributions (PDI < 0.20) with size stability for up to 30 days. Encapsulation efficiencies were 37% for CUR and 82% for 5-FU, with sustained drug release profiles showing 50% of CUR and 70% of 5-FU released over 72 h. In vitro studies demonstrated sustained cytotoxic effects, and cell cycle arrest at the G2/M phase in breast cancer cell lines, with minimal toxicity in non-cancerous cells. Cellular uptake assays confirmed efficient drug delivery to the cytoplasm. In vivo biodistribution studies revealed increased tumour-specific drug accumulation with magnetic guidance. Haematoxylin & Eosin (H&E) staining indicated enhanced tumour necrosis in treated groups compared to controls. Conclusions: This study underscores the utility of the swirl mixer for efficient and scalable fabrication of bio-inspired SFPs, supporting their application in targeted cancer drug delivery. These findings align with and advance previous insights into the use of microfluidics and desolvation methods, paving the way for improved therapeutic strategies in breast cancer treatment.